Physical, mechanical, and electrical properties of rice starch-based films plasticised by ionic liquid. Issue 4 (8th August 2022) - Roy, Joydev; Bhattacharya, Suvendu; Sahu, Partha Pratim; Das, Amit Baran
ABSTRACT: A biodegradable film was developed using an ionic liquid as a plasticiser, and rice starch having medium amylose content. The physical, mechanical and electrical properties of the developed films were determined and analysed employing the principles of chemometrics. The water vapour transmission and elongation of the films increased with 1-butyl-3-methylimidazolium chloride (BMIMCl) concentration. The highest melting temperature was 133.4°C when the concentration of BMIMCl was 4% (w/w). The crystallinity and extent of modification were characterised by XRD and FTIR. The highest conduction of film was 0.29 S/m while the lowest resistance observed was 3.42 Ωm. The chemometric analysis of parameters of the film was carried out in terms of hierarchical cluster analysis (HCA) and principal component analysis (PCA). This study demonstrated the possibility of using rice starch with BMIMCl as the plasticiser to design an electroconductive film having the desired heating characteristics. GRAPHICAL ABSTRACT: UF0001